Labor market integration of foreign students: The role of native peers - Asbjørn Juul Petersen (University of Copenhagen, Department of Economics, Center for Economic Behavior and Inequality (CEBI), 2024)
I investigate what affects foreign students' decision to stay and work in the host country after completion of higher education. Specifically I ask whether the network of native peers at university affect the probability that foreign students in Denmark stay in the country and find employment after ended studies. To identify the causal effects, I exploit idiosyncratic variation in the share of Danish students who are admitted into each study program over adjacent cohorts. I find that an increase in the share of native peers of one standard deviation increases the probability that foreign students are employed in Denmark two years after ended studies by 4 pct. points. The effects are significant at least four years after ended studies. Improved professional network and knowledge of the Danish labor market seem to be an important mechanism.
Keywords: F66; I21; J22; 330; Foreign students; labor supply; peer effects; higher education